Involuntary and voluntary memory retrieval relies on distinct neural representations and oscillatory processes. - Malte Kobelt; Gerd T Waldhauser; Marie-Christin Fellner; Nikolai Axmacher (PLoS Biology)
Involuntary memory retrieval is a hallmark symptom of posttraumatic stress disorder and a frequent phenomenon in everyday autobiographical memory. However, the neural mechanisms that drive involuntary retrieval remain unclear. This study aims to elucidate how involuntary retrieval spontaneously initiates memory reactivation and how the reactivated neural representations differ in their content, distinctiveness and temporal compression from voluntary retrieval. Combining a visual half-field paradigm with electroencephalography recordings (EEG) in humans, we tracked reactivation of item-specific neural representations and sensory feature representations measured as representational similarity between different items sharing the same sensory feature - the visual field at encoding. We show that involuntary retrieval reactivated sensory feature-dependent yet item-unspecific representations via temporally extended memory replay, accompanied by rapid mid-frontal theta-power increases, indicating memory interference. This neural process differed from voluntary retrieval which recruited goal-directed memory search processes in prefrontal-medial temporal lobe theta-bands to reactivate temporally compressed item-specific representations devoid of visual field specific sensory feature representations at encoding. Our findings demonstrate that involuntary memories rely on distinct neural processes that access different representational formats compared to voluntary retrieval offering a nuanced understanding of episodic memory functioning relevant to psychological well-being.